Visually Induced Motion Sickness Susceptibility and Recovery Based on Four Mitigation Techniques - Jasper, Angelica; Cone, Nicholas; Meusel, Chase; Curtis, Michael; Dorneich, Michael C.; Gilbert, Stephen B. (Frontiers in Virtual Reality, 2020)
Virtual reality (VR) usage continues to grow, but visually induced motion sickness (VIMS) can decrease VR effectiveness for some users. This study seeks to compare methods of VIMS mitigation and explore sickness among gender and video game experience groups. Participant discomfort and early dropout are problems for studies that involve virtual environment (VE) exposure, but previous research has demonstrated that natural decay and physical, real-world hand-eye coordination tasks can serve as effective mitigation strategies. In this study, 57 participants wore a head-mounted display (HMD) and navigated a maze VE designed to induce cybersickness. Participants then experienced one of four mitigation techniques: real natural decay (HMD off), virtual natural decay (HMD on with idyllic VE and no locomotion), real hand-eye coordination task (HMD off), and virtual hand-eye coordination task (HMD on). Simulator Sickness Questionnaire (SSQ) measures were taken periodically throughout maze and mitigation tasks. Results demonstrated that peak sickness during the maze VE occurred after approximately 10 minutes. Analyses of mitigation techniques showed that real natural decay resulted in significantly more sickness recovery when compared with the virtual hand-eye coordination task for SSQ total score, nausea, and oculomotor constructs, but not disorientation. The real natural decay technique was the most effective at bringing participants' final sickness measure back to their initial baseline measure; however, other mitigation techniques yielded effectiveness, but at a lower rate. This study extends previous research about hand-eye mitigation approaches by demonstrating that natural decay and hand-eye tasks in a virtual and real-world setting were effective in reducing VIMS. Real-world natural decay was the most effective at mitigating VIMS and the virtual hand-eye task was not as effective as the other three tasks. Women experienced more VIMS that men, but also recovered more than men during mitigation. Video gamers experienced less VIMS than non-gamers. These findings bolster extant knowledge about VIMS mitigation techniques and can inform future development of virtual mitigation techniques.